Baicalein blocks α-synuclein secretion from SN4741 cells and facilitates α-synuclein polymerization to big complex. (10th August 2017) - Li, Xingjian; Zhang, Guofeng; Nie, Qi; Wu, Ting; Jiao, Luyan; Zheng, Meige; Wan, Xiaomei; Li, Yonglin; Wu, Song; Jiang, Bin; Xiang, Xianhong; Duan, Jinhai; et al.
Highlights: BAI may block the secretion of α-syn, probably through enhancing macroautophagy. BAI upregulated the cell viability of SN4741 cells expressing W-syn or A53T-syn. BAI facilitated α-syn (19–72 kDa) aggregation into big complex states (above 72 kDa), which could lead to the propagation of α-syn down-regulated. Abstract: The secretion of α-synuclein (α-syn) acts as an essential driver in the propagation of synucleinopathies in brain. The clearance of extracellular α-syn or blockade of the cell-to-cell transmission of α-syn is a promising approach to prohibiting synucleinopathies propagation. Baicalein (BAI), a flavonoid from Chinese herb, has been reported to bind covalently to α-syn to inhibit α-syn fibrillation and degrade its fibrils. However, whether BAI inhibits α-syn secretion is unclear. Here we showed that BAI reduced α-syn in the media of dopaminergic cell lines (SN4741) overexpressing wild-type α-syn (W-syn) or A53T mutant type α-syn (A53T-syn), while increased α-syn expression in cell lysates, upregulated the cell viability and increased the ratio of LC3 II/LC3 I, the latter is an indicator reflects the macroautophagic level. Intriguingly, BAI did not clear extracellular α-syn directly but facilitated α-syn polymerization to big complex (over 72 kDa), which revealed that BAI probably reduced α-syn transmission by facilitating α-syn polymerization to big complex. Taken together, BAI could be a potential drug to inhibit α-syn propagation among the neurons.